Aeromonas salmonicida: A very rare but potential threat to human - Tawari, Nishant; Agrawal, Rajesh (Indian Journal of Child Health, 2024)
Aeromonas salmonicida is a ubiquitous Gram-negative bacterium. It mainly found in aquatic ecosystem. It is most common pathogen in salmonids. Reported infections due to A. salmonicida in humans are very rare. A 5-year-old child admitted with fever since more than a week and loose motions. The blood culture showed growth of A. salmonicida. The child responded well to intravenous antibiotics and discharged after 5 days of admission. A. salmonicida is a rare but potential pathogen for human infections. Modern diagnostic methods are being effective in diagnosing it and empirical antibiotics (Cephalosporin) are helpful in treating it.